Pengaruh Penggunaan Media Mading terhadap Keterampilan Menulis Teks Narasi Siswa Sekolah Dasar: The Influence of Using Wall Magazine Media on Elementary School Students' Narrative Text Writing Skills - Minarti Minarti; Saifullah Saifullah; Aswadi Aswadi; Suleha Ecca (Information Technology and Science(ITScience), 2026)
Narrative writing skills are important for elementary school students, but many still struggle to develop ideas, organize plots, and use language appropriately. This problem is also influenced by the use of less varied, less interesting learning media. Therefore, this study aims to analyze the effect of using wall magazines (mading) on students' narrative text-writing skills. This study uses a quantitative, quasi-experimental approach with a One-Group Pretest–Posttest design. The study subjects were 27 students in grades III and IV of SD Negeri Satap 12 Batu, Leppangeng Village, selected using a total sampling technique. The research instruments were narrative text writing and documentation tests, and data analysis used descriptive and inferential statistics, including paired-samples t-tests. The results showed a difference in students' average scores, from 56.48 on the pretest to 80.00 on the posttest, as well as a change in learning completeness from 7.41% to 100%. The results of the hypothesis test showed a p-value of 0.000 (<0.05), indicating a significant effect of wall magazine media on students' narrative writing skills. Thus, the use of wall magazine media has been shown to affect changes in elementary school students' narrative writing skills and can serve as an innovative learning medium.